Repeated administration of fenitrothion alters renal functions via oxidative stress mechanism without inhibiting acetylcholinesterase activity in rats - Yusoff, Nur Afizah; Juremi, Izzah Irdina; Budin , Siti Balkis; Taib, Izatus Shima (Life Sciences, Medicine and Biomedicine, 2020)
Background: The main mechanism of fenitrothion (FNT) toxicity is by inhibiting the acetylcholinesterase enzyme, though studies have shown that FNT might also develop other toxicological manifestations, including oxidative stress. However, the kidney functions as well as oxidative stress status after repeated exposure to FNT is not well documented. Objective: The present study was conducted to evaluate the kidney functions and oxidative stress status after exposure to low doses of FNT. Materials and Methods: 24 male Sprague-Dawley rats were divided randomly into three groups (n = 8/group): control, which received 1 mg/ml corn oil; FNT 10, which received 10 mg/kg (BW) FNT; and FNT20 which received 20 mg/kg (BW) FNT. The corn oil and FNT were fed orally for 28 consecutive days. At the end of the study, the blood was taken, and the kidney was obtained for biochemistry evaluation and histological observation. Results: The AChE activity was significantly inhibited in the FNT20 group (p≤0.05) compared to the control group and FNT10 and the rats exhibited the signs and symptoms of toxicity such as lacrimation, piloerection, hypoactivity, and tremor. Plasma creatinine and BUN levels showed a significant increase (p≤0.05) in FNT treated groups, but the superoxide dismutase and glutathione level were significantly reduced (p≤0.05). The malondialdehyde and protein carbonyl level were elevated significantly (p≤0.05) in FNT treated groups. Histopathological observation revealed morphological changes, including atrophy of the glomerulus and presence of non-amyloid substances in FNT treated groups. Conclusion: Even at the dose that did not inhibit the AChE activity, FNT was found to reduce the renal function and induce oxidative damage on the kidney of male Sprague Dawley rats.